Frictional Resistance in Various Ceramic Brackets using Archwires of different Alloys, Sizes and Cross sections: A Comparative Study - Bahadur, Yash Raj; Agarwal, Deepak Kumar; Gupta, Ankur; Prasad, P Narayana (Orthodontic Journal of Nepal, 2016)
Introduction: Friction at the bracket-archwire interface has been observed as one of the most important factors affecting tooth movement. Hence it is importance to assess the friction generated during tooth movement to bring about optimal treatment results. Objective: To compare the frictional resistance of various ceramic brackets using different archwires, and to compare the static and kinetic frictional force of various ceramic brackets using different archwires. Materials & Method: The present study evaluated and compared the friction generated at the bracket archwire interface when 0.018” and 0.019”x0.025” stainless steel archwires and 0.019”x0.025” teflon coated stainless steel archwires were moved through conventionally ligated, passive self-ligating and interactive self-ligating ceramic brackets. The static and kinetic frictional forces were also evaluated and compared. Result: Highly significant differences in kinetic (p<0.001) and static (p<0.001) frictional forces were observed in all three groups when used with the different archwires. On comparing the static and kinetic frictional forces significant differences were observed among all three groups (p<0.05). Conclusion: The passive self-ligating brackets produce the least frictional forces when compared to interactive self-ligating and conventionally ligated brackets. Also, the static frictional forces were found to be more as compared to kinetic frictional forces. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.18-22